Austerity, growth and inflation: Remarks on the Eurozone's unresolved competitiveness problem - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2013)
While the financial protection measures enacted by the ECB and the community of Eurozone members have calmed financial markets, they have left the competitiveness problem of the Eurozone's southern countries and France unresolved. The paper compares price inflation before the crisis with the necessary and actual price cuts that have taken place since the outbreak of the crisis, predicting a decade of stagnation for the south and inflation for the north. Keynesian demand policy is counterproductive in the south and unnecessary in the north. The necessary realignment of relative goods prices and current account imbalances can be achieved if market forces are allowed to redirect capital flows to the north instead of being artificially steered to uses they are keen to avoid.
Keywords: E31; E61; E62; F31; F32; F34; H62; H63; 330; competitiveness; inflation; realignment; Keynesian policy; Zahlungsbilanzungleichgewicht; Internationaler Wettbewerb; Inflation; Austeritätspolitik; Globalsteuerung; Entwicklungskonvergenz; Eurozone; Südeuropa